The benefits of the water impounding project to the Irragators' Association at Barangay Capunang, San Dionisio, Iloilo. - Territorio, Lorena S. (1980.)
The evaluation of the Capinang Water Impounding Project through the farmer members of the Capinang Irrigators' Association is made to asses the impact of the project in the socio-economic life of the direct beneficiaries. This also aims to point out the problems that have developed in the course of the implementation of the project in the mentioned area., Eleven out of twelve members of the Irrigators' Association were interviewed in this study since one of the target respondent was not available at the time of data collection. The findings reveal that the Capinang Water Impounding Project is still far from reaching the goals and objectives set at the start of the project. The result shows that only three out of the twelve direct beneficiaries of the Irrigators' Association are benefited by the irrigation facilities of the Water Impounding. This mainly due to the inadequacy of the Water Impounding Dam to store enough water to meet the irrigation needs of the farmers in the area. The dam has only a limited reservoir capacity which can not support the farming needs of the farmers in Capinang. Specifically, only the irrigation service which in itself is limited to a number, had been set by the Water Impounding Project in the area. No other social or economic benefits have been derived from such since its implementation and operation in 1974.
Papers (Undrgraduate, Bachelor of Arts in Social Sciences) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Irrigators' Association -- San Dionisio, Iloilo